AUDIT OF LEIOMYOMA UTERUS AT KHYBER TEACHING HOSPITAL PESHAWAR - Begum, Shamshad; Khan, Sameera (Journal of Ayub Medical College Abbottabad, 2004)
Background: Fibroid is the commonest tumor of the reproductive tract and frequently encountered problem in gynecological practice. This study was carried out to observe the frequency of fibroids in relation to age, parity and clinical manifestations along with a critical review of its management. Methods: This study was carried out over a period of one year from 1st January to 31st December 2000 in Gynae A unit of Khyber teaching hospital, Peshawar. All patients presenting with fibroid uterus were included in the study. Data collection included age, parity, menstrual pattern, presenting symptoms, medical and surgical treatment history. Diagnostic criteria were clinical and ultrasonography. Evaluation of medical treatment and surgery were carried out. Management outcome of minimal invasive surgery was also observed. Results and Conclusion: Total 146 cases were observed. Greater frequency was found in late reproductive and perimenopausal years (65.7%). There were 34.2% cases in reproductive age group. Majority was multiparous (72%) and 28% were nulliparous. Infertility was noticed in 16%. Myomas were mostly symptomatic (70%). Menstrual symptoms were commonest (81.5%), pain was second common symptom (27.3%). About 24% presented with abdominal mass and hyaline degeneration were in 50% of cases. Leiomyomas were multiple in 63.1% and commonest variety was interstitial (60.4%). Familial factor noticed in 5.4%, clinical diagnosis was made in 58.2% of cases, while ultrasound was used in 40.4% of patients, conservative treatment was given in 37.6% including medical therapy (8.2%), Surgery was performed in (62.3%). .Myomectomy (10.2%) and hysterectomy was carried out in 52.05%. Minimal invasive surgery was not possible in our set up. KeyWords: Leiomyoma, menorrhagia, degenration, myomectomy, hystrectomy, Fibroid uterus